The potential of using technology to support personalised learning in low- and middle-income countries - Major, Louis; Francis, Gill (EdTech Hub, 2020)
With schools around the world closed to prevent the spread of COVID-19, we have been undertaking a series of ‘rapid evidence reviews’ to help education decision-makers respond effectively. These reviews aim to provide evidence-based summaries on specific areas of EdTech. In this post, we look at the role of technology in supporting personalised…
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Technology-Supported Personalised Learning: A Rapid Evidence Review - Major, Louis; Francis, Gill A. (EdTech Hub, 2020)
This publication is one part of a series of rapid evidence reviews that has been produced by the EdTech Hub. The purpose of the rapid evidence reviews is to provide education decision-makers with accessible evidence-based summaries of good practice in specific areas of EdTech. They are focused on topics which are particularly relevant in the context of widespread global challenges to formal schooling as a result of COVID-19. All the rapid evidence reviews are available at edtechhub.org.
Keywords: F: Evidence review; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v3; _zenodo:submitted; _zenodoETH

EdTech for Learners with Disabilities in Primary School Settings in LMICS: A Systematic Literature Review - Lynch, Paul; Singhal, Nidhi; Francis, Gill A. (EdTech Hub, 2021)
This systematic literature review was guided by the overarching aim of establishing the categories of EdTech that may be appropriate to support the learning of children with disabilities aged 4–12 years in low-and middle-income countries. A critical review of the published literature was deemed essential as the field of disability and EdTech (mirroring larger trends in disability and educational research) has remained dominated by anecdotal commentaries and strong personal assertions, but substantiated by little evidence. In framing the review we drew on a dual model of access which provides a helpful lens into how EdTech can support a learner’s development trajectory across different interventions (e.g. learning to read Braille or sign language), targeted educational outcomes, inclusive practices and suitable accommodations in different educational settings. This approach is underpinned by a human rights agenda, as articulated in the UN Convention for the Rights of Persons with Disabilities (CRPD) and the Sustainable Development Goals (SDGs) which demand fair and equal access to education for all children and young people. They are also concerned, though, that an individual child/young person should have agency, self-determination and independence. Article 2 of the CRPD unambiguously recognizes that reasonable accommodation is vital in enabling persons with disabilities to enjoy and exercise their rights on an equal basis with others.
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodoETH

How Can EdTech Support Primary School Learners with Disabilities in LMICs? Recommendations for Policy - Lynch, Paul; Singal, Nidhi; Francis, Gill A. (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v3; _r:AddedByZotZen; _zenodo:submitted; _zenodoETH

The effectiveness of technology-supported personalised learning in low- and middle-income countries: A meta-analysis - Major, Louis; Francis, Gill A.; Tsapali, Maria (British Journal of Educational Technology, 2021)
Digital technology offers the potential to address educational challenges in resource-poor settings. This meta-analysis examines the impact of students' use of technology that personalises and adapts to learning level in low- and middle-income countries. Following a systematic search for research between 2007 and 2020, 16 randomised controlled trials were identified in five countries. Studies involved 53,029 learners aged 6–15 years. Coding examined learning domain (mathematics and literacy); personalisation level and delivery; technology use; and intervention duration and intensity. Overall, technology-supported personalised learning was found to have a statistically significant—if moderate—positive effect size of 0.18 on learning (p = 0.001). Meta-regression reveals how more personalised approaches which adapt or adjust to learners' level led to significantly greater impact (an effect size of 0.35) than those only linking to learners' interests or providing personalised feedback, support, and/or assessment. Avenues for future research include investigating cost implications, optimum programme length, and teachers' role in making personalised learning with technology effective. Practitioner notes What is already known about this topic? Promoting personalised learning is an established aim of educators. Using technology to support personalised learning in low- and middle-income countries (LMICs) could play an important role in ensuring more inclusive and equitable access to education, particularly in the aftermath of COVID-19. There is currently no rigorous overview of evidence on the effectiveness of using technology to enable personalised learning in LMICs. What this paper adds? The meta-analysis is the first to evaluate the effectiveness of technology-supported personalised learning in improving learning outcomes for school-aged children in LMICs. Technology-supported personalised learning has a statistically significant, positive effect on learning outcomes. Interventions are similarly effective for mathematics and literacy and whether or not teachers also have an active role in the personalisation. Personalised approaches that adapt or adjust to the learner led to significantly greater impact, although whether these warrant the additional investment likely necessary for implementation at scale needs to be investigated. Personalised technology implementation of moderate duration and intensity had similar positive effects to that of stronger duration and intensity, although further research is needed to confirm this. Implications for practice and/or policy: The inclusion of more adaptive personalisation features in technology-assisted learning environments can lead to greater learning gains. Personalised technology approaches featuring moderate personalisation may also yield learning rewards. While it is not known whether personalised technology can be scaled in a cost-effective and contextually appropriate way, there are indications that this is possible. The appropriateness of teachers integrating personalised approaches in their practice should be explored given ‘supplementary’ uses of personalised technology (ie, additional sessions involving technology outside of regular instruction) are common.
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _zenodo:submitted; computer-assisted learning; learning outcomes; low- and middle-income; meta-analysis; personalisation; personalised adaptive learning; ⛔ No DOI found

EdTech for learners with disabilities: urgent need to focus on access, engagement and learning outcomes - Singal, Nidhi; Lynch, Paul; Kaye, Tom; Francis, Gill (EdTech Hub, 2021)
The current approaches to providing high quality learning experiences to learners with disabilities in low and middle-income (LMICs) countries requires radical rethinking. To date, significant numbers of learners with disabilities are not enjoying the benefits of barrier-free and meaningful engagement with the school curriculum in order to reach their potential. Appropriately matched technology to learner needs – in terms of…
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Position paper: EdTech for learners (internal working paper). - Damani, Kalifa; Francis, Gill; McIntyre, Nora; Major, Louis; Hollow, David (EdTech Hub, 2020)
Keywords: _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _dont_post_PDF

Educational technology for learners with disabilities in primary school settings in low- and middle-income countries: a systematic literature review - Lynch, Paul; Singal, Nidhi; Francis, Gill Althia (Educational Review, 2022)
Educational Technology (EdTech) plays a significant role in enabling learners with disabilities to access learning at school and reduce educational and social exclusion. It also enables them to enjoy the benefits of a full school curriculum and to participate in activities in different educational arrangements. The purpose of this review was to address the existing evidence of how EdTech is being used to support learners with disabilities in order to inform future research and policymaking. It sought to contribute to an evidence base of ways to reduce barriers to learning drawing on a systematic methodology to gather evidence pertaining to access to EdTech for primary school learners with disabilities aged 6–12 years. After a thorough examination of the literature, the final sample comprised 51 published articles (43 peer-review and 8 conference papers). The review revealed examples of positive outcomes of EdTech interventions being used, particularly in special schools; however, the evidence of their efficacy is weak. The use of EdTech for learners with disabilities in low- and middle-income countries requires further, robust and long-term research that considers the involvement of learners, pedagogy and curriculum design in order to understand its impact on improving educational experiences of children with disabilities.
Keywords: Educational technology; assistive technology; disability; inclusive education; low- and middle-income countries; primary education

Educational technology for learners with disabilities in primary school settings in low- and middle-income countries: a systematic literature review - Lynch, Paul; Singal, Nidhi; Francis, Gill Althia (Educational Review, 2022)
Keywords: ⛔ No INSPIRE recid found